2006
DOI: 10.1007/bf03022615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thiopental sodium on N-methyl-D-aspartate-gated currents

Abstract: Purpose: N-methyl-D-aspartate (NMDA) receptors in the prefrontal cortex (PFC) are closely related with the excitability of pyramidal neurons and PFC function. As the effect of thiopental sodium on the central nervous system may partly result from the inhibition of PFC NMDA receptors, we investigated the effect of thiopental sodium with different concentrations on NMDA-gated currents in acutely dissociated rat PFC pyramidal neurons. We sought to determine whether thiopental sodium inhibits NMDA receptor functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…Combined with these observations, we suggest that thiopental produce loss of righting reflex, at least in part, through an inhibition of NMDA receptor in mice. A previous study, which indicated that thiopental decreased NMDA-gated currents in acutely dissociated rat prefrontal cortical pyramidal neurons in a concentration-dependent manner [6] , supports our conclusion. In the present study, NMDA only partly attenuated but did not completely reverse thiopental action.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Combined with these observations, we suggest that thiopental produce loss of righting reflex, at least in part, through an inhibition of NMDA receptor in mice. A previous study, which indicated that thiopental decreased NMDA-gated currents in acutely dissociated rat prefrontal cortical pyramidal neurons in a concentration-dependent manner [6] , supports our conclusion. In the present study, NMDA only partly attenuated but did not completely reverse thiopental action.…”
Section: Discussionsupporting
confidence: 79%
“…Previous observations strongly implicate the GABA A receptor as a molecular target relevant to the general anesthetic action of thiopental [3,4] . However, thiopental with clinically related concentrations also attenuates the release of glutamate from rats' prefrontal cortical synaptosomes and glutamate receptor-mediated excitatory neurotransmission in the mouse cortex [5,6] . These in vitro findings suggest that thiopental also inhibits glutamate receptor-mediated excitation in the CNS.…”
mentioning
confidence: 99%
“…Although myoclonus is explained as not being generated by an epileptic focus, the effect of reduction in myoclonus may occur by means of a 2 -adrenoceptor agonism. Using a concentration-dependent method, Liu et al concluded that NMDA-gated currents were acutely reduced by thiopental sodium dissociated rat prefrontal cortical pyramidal neurons [19]. Via these mechanisms, the drug has a common use in sedation, hypnosis, and general anesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…For experiments with pharmacological agents, doses of thiopental (1 mM; Sigma, St Louis, MO, USA) and nicotinamide (1 mM; Sigma), known elicit responses in other tissues, were added to the media 48 49…”
Section: Methodsmentioning
confidence: 99%